Customer Incivility and Employee Silence: A Short-Longitudinal Model Relationship and Its Effect on Turnover Intention - Sugiono, Edi; Achmadi, Achmadi; Hendryadi, Hendryadi; Gustiawan, Deni; Gusliana Mais, Rimi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
The main objective of this study is to explore the dynamic relationship between customer incivility and employee silence in the hospitality sector over time. In addition, turnover intention as an outcome of workplace incivility and employee silence is also analyzed. The data was collected from two waves of 226 frontline employees from six hotels to test the proposed model. PLS-SEM analysis revealed a stable relationship between workplace incivility and employee silence at Time 1 and 2, respectively. This study also shows that workplace incivility is positively related to employee silence, and in the future, employee silence is also positively associated with customer incivility. Furthermore, both workplace incivility and employee silence are predictors of turnover intention. This study offers theoretical and practical implications for future researchers and practitioners to study employee silence and incivility in the hospitality sector.